EXISTENCE OF GENERAL COURSES: A STUDY OF ACEHNESE HISTORY AND CULTURE AS A COMPULSORY SUBJECT AT SAMUDRA UNIVERSITY - Usman Usman; Bachtiar Akob; Rahmatsyah Rahmatsyah; Asnawi Asnawi; Bukhari Bukhari; Zulfiani Zulfiani (Universitas Negeri Medan, 2023)
In the vision and mission of Samudra University